Pengaruh Partisipasi Pelatihan, Responsibility dan Motivasi Kerja terhadap Kinerja Kepala Desa di Kabupaten Gorontalo - Mohamad, Roni (Al-Buhuts, 2019)
The aims of this research to determines the effect of participation in training, work responsibility, work motivation towards the performanceon a head of village at Gorontalo Regency. These research was conducted at Gorontalo local government that involved sample 137 head of Village. To determine sample selected by proportionate random sampling technique. Collecting data by using Likert scale consists of five option. Meanwhile the data analyzed with path analysis. The results are: (1) Participation in Training directly positive affects performance, (2) Work Responsibility directly positive affects performance, (3) Work motivation had a direct positive impact on performance, (4) Participation in training directly positive influence work motivation, (5 ) Work Responsibility directly positive influence work motivation. Based on this research, Participation in training, work responsibility, work motivation has direct positive effect on a head of village performance. Futhermore it should be developed by Regency goverment, and central governance to make be better of performance head of village